Penerapan Asas Kekeluargaan Dalam Sistem Pengendalian Internal Pemberian Kredit Di Koperasi Kredit Swastiastu - Satriadi, Komang Ryan Krisna; Dewi, Ni wayan Yulianita (Universitas Pendidikan Ganesha, 2020)
Â This study aimed to determine how was the implementation of kinship principle in the internal control system of credit provision in Swastiastu Credit Cooperative. Swastiastu Credit Cooperative is a type of savings and loan cooperative that has good potential and performance so that in 2019, Swastiastu Credit Cooperative is one of the cooperatives based on representing the province of Bali and already has cooperative branches in each region. This study applied qualitative methods. The data used in this study are primary data and secondary data with data collection methods using interviews, observation and documentation. The object of research is the Swastiastu Credit Cooperative and the informants of this study are from the management of the Swastiastu Credit Cooperative. The techniques used in data analysis are data reduction, data presentation, data analysis and conclusion drawing. The conclusion of this study states that the application of the principle of kinship as a system of internal control of granting credit remains based on the law. However, in its application, the principle of kinship applies to the making of initial agreements for loan applications and monitoring and coaching in repaying loans. With the application of the principle of kinship can minimize the amount of bad credit in the Singaraja Swastiastu Credit Cooperative